Quantitative schlieren diagnostics for the determination of ambient species density, gas temperature and calorimetric power of cold atmospheric plasma jets. (31st March 2015) - Schmidt-Bleker, A; Reuter, S; Weltmann, K-D
Abstract: A measurement and evaluation technique for performing quantitative Schlieren diagnostics on an argon-operated cold atmospheric plasma jet is presented. Combined with computational fluid dynamics simulations, the method not only yields the temporally averaged ambient air density and temperature in the effluent of the fully turbulent jet, but also allows for an estimation of the calorimetric power deposited by the plasma. The change of the refractive index due to mixing of argon and air is in the same range as caused by the temperature increase of less than 35 K in the effluent of the plasma jet. The Schlieren contrast therefore needs to be corrected for the contribution from ambient air diffusion. The Schlieren system can be calibrated accurately using the signal obtained from the argon flow when the plasma is turned off. The temperature measured in this way is compared to the value obtained using a fibre-optics temperature probe and shows excellent agreement. By fitting a heat source in a fluid dynamics simulation to match the measured temperature field, the calorimetric power deposited by the plasma jet can be estimated as 1.1 W.